Effect of supporting implants inclination on stability of fixed partial denture: A finite element study. (October 2020) - Boukhlif, Amel; Merdji, Ali; Roy, Sandipan; Alkhaldi, Hashem; Abu-Alshaikh, Ibrahim; Della, Nourddine; Cristache, Corina Marilena; Hillstrom, Rajshree
The aim of this finite element study was to analyze effect of supporting implants inclination on stress distribution in the bone for a four-unit fixed partial denture. A three-dimensional finite element model of mandibular molar section of the bone to receive implants was constructed. Three implant-supported fixed partial dentures, with null, moderate and wide tilting, of 0°, 15° and 30° implant inclinations, respectively, were modeled. A mechanical load of 10 MPa was applied in coronal–apical direction on bridge framework at the regions of crowns positions. The finite element analysis was performed, and von Mises stress levels were calculated. Peak stress concentration in the cortical bone was observed mostly around the implant necks, in inter-implants line. There was favorable stress distribution during loading, with peak stress being 90.04 MPa for 0°, which decreased to 54.33 MPa for 15° and 46.36 MPa for 30° inclination. The supporting implants inclination in fixed partial denture plays an important role in stress distribution and may be helpful in preventing bone loss and implant failure. This phenomenon is likely to be more pronounced in bones of poor quality. Within the limitation of this study, it seems that the inclination of implants in fixed partial denture has a favorable effect on stress distribution pattern values around the supporting implants.